PERENCANAAN BENDUNG DAMAR KABUPATEN KENDAL, JAWA TENGAH - Suhardi Suhardi; Yandi Purbangsa; Sri Eko Wahyuni; Sugiyanto Sugiyanto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Damar weir is a hydraulic structure which will construct in Pageruyung village, Kendal district. The objective of Damar weir construction is designed to fulfill the needs of irrigation water for the rice fields around the area. According to the analysis the flood discharge plan of Damar weir is 111 m3/sec with 50 years return period. The weir is using a rounded crest weir with effective width 23,7 m and height of the crest is 2,5 m. The length of the upstream apron floor is 3,0 m and uses the USBR Type IV stilling basin. The length of the sand trap is 40 m with the width of channel base 1,5 m. The time schedule of this project is 28 weeks and the budget plan is Rp 10.185.086.00,00 (Ten Billion, One Hundred And Eighty Five Million, Eighty Six Thousand Rupiah).